Concentrations of cardiac troponin T in neonates with and without respiratory distress. Issue 4 (21st June 2004) - Clark, S; Newland, P; Yoxall, C W; Subhedar, N V
Abstract : Aims: To establish a practical postnatal reference range for cardiac troponin T in neonates and to investigate concentrations in neonates with respiratory distress. Methods: Prospective investigation in a tertiary neonatal unit, recruiting infants with and without respiratory distress (sick and healthy infants respectively). Concentrations of cardiac troponin T were compared between sick and healthy infants, accounting for confounding variables. Results: A total of 162 neonates (113 healthy and 49 sick infants) had samples taken. The median (interquartile range) cardiac troponin T concentration in the healthy infants was 0.025 (0.01–0.062) ng/ml, and the 95th centile was 0.153 ng/ml. There were no significant relations between cardiac troponin T and various variables. The median (interquartile range) cardiac troponin T concentration in the sick infants was 0.159 (0.075–0.308) ng/ml. This was significantly higher (p < 0.0001) than in the healthy infants. In a linear regression model, the use of inotropes and oxygen requirement were significant associations independent of other basic and clinical variables in explaining the variation in cardiac troponin T concentrations. Conclusions: Cardiac troponin T is detectable in the blood of many healthy neonates, but no relation with important basic and clinical variables was found. Sick infants have significantly higher concentrations than healthy infants. The variations in cardiac troponin T concentration were significantly associated with oxygen requirement or the use of inotropic support in a regression model. Cardiac troponin T may be a useful marker of neonatal and cardiorespiratory morbidity.